INVENTARISASI ARECACEAE DI KAWASAN WISATA AIR TERJUN IRENGGOLO KEDIRI - Antoni, Herman Wayudi; Ratnasari, Deny; Nurmilawati, Mumun; Santoso, Agus Muji (Universitas Sebelas Maret, 2014)
Abstract-Arecaceae is a monocot that grows in parts of the world from the tropics and sub-tropics, lowlands to highlands, on the mountains and the shore, in the lush and barren land. From the 215 genus of Arecaceae, the 46 genus is growing in Indonesia and 29 of them is endemic plant. Lately, Aracaceae research related to rare, whereas the benefits of it is good among other for drugs, cosmetics, building materials, and others. The study aims to determine the species of Arecaceae in the waterfall region of Irenggolo Kediri. Descriptive study was conducted with the observation and literature review technique. Samples were taken with a random roaming method which is divided into four zones according to the height of land. The Arecaceae found in Irenggolo waterfall Kediri as many as of six species, namelyÂ A. pinnata, P. roconata, Daemonorops sp., Calamus unifarius, Calamus sp., S. Zalampaicc.Â Keywords :inventory, Arecaceae, waterfall, Irenggolo